2020
DOI: 10.3233/jad-191114
|View full text |Cite
|
Sign up to set email alerts
|

Late-Life Physical and Cognitive Activities Independently Contribute to Brain and Cognitive Resilience

Abstract: Background-Active lifestyles are related to better cognitive aging outcomes, yet the unique role of different types of activity are unknown. Objective-To examine the independent contributions of physical (PA) versus cognitive (CA) leisure activities to brain and cognitive aging. Methods-Independent samples of non-demented older adults from University of California, San Francisco Hillblom Aging Network (UCSF; n = 344 typically aging) and University of California, Davis Diversity cohort (UCD; n = 485 normal to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 55 publications
7
39
2
Order By: Relevance
“…In our study, CA, not PA, was found to be significantly associated with the domain‐specific cognition. These findings are consistent with other large sample observational surveys where the independent value of CA and PA was examined 22,30‐35,38‐42 . Clare and Najar reported that CA and PA were both independently associated with better cognitive function and lower risk of developing dementia 38,39 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, CA, not PA, was found to be significantly associated with the domain‐specific cognition. These findings are consistent with other large sample observational surveys where the independent value of CA and PA was examined 22,30‐35,38‐42 . Clare and Najar reported that CA and PA were both independently associated with better cognitive function and lower risk of developing dementia 38,39 .…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with other large sample observational surveys where the independent value of CA and PA was examined. 22,[30][31][32][33][34][35][38][39][40][41][42] Clare and Najar reported that CA and PA were both independently associated with better cognitive function and lower risk of developing dementia. 38,39 In two independent samples of non-demented older adults, Casaletto et al and his colleagues found higher CA, but not PA was related to better global cognition.…”
Section: Association Of Combined Ca and Pa With Domain-specific Cogmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, environmental stimuli during the early life period can exert prominent effects on the risk of neurological disorders (Lesuis et al, 2018 ). In this regard, a considerable number of scientific publications have reported that the combination of both physical and cognitive stimulation can affect brain resilience (Deuster and Silverman, 2013 ; Bozzali et al, 2015 ; Pedrinolla et al, 2017 ; Casaletto et al, 2020 ). The literature has clearly demonstrated that an active lifestyle is inversely associated with stress-related health problems resulting in the development of chronic diseases (Deuster and Silverman, 2013 ; Clark et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…[0.05] / comparisons per model[127]). 61.29% of these effects were observed for composite proxies including cognitively stimulating activities, which was not available in CR/RANN.…”
mentioning
confidence: 99%